Bilateral Tibial Tubercle Sleeve Fractures in a Skeletally Immature Patient - Rasesh R. Desai; Shital N. Parikh (Case Reports in Orthopedics)
Tibial tubercle sleeve fracture is a rare injury. In concept, it is similar to the patellar sleeve fracture in a skeletally immature patient. We describe a unique case of simultaneous bilateral tibial tubercle sleeve fractures in a 12-year-old boy. Radiographs and MRI confirmed the injury. The patient underwent open surgical repair of bilateral sleeve fractures with suture anchor fixation. At the final followup, 3 years after his initial injury, the patient demonstrated full knee function bilaterally without radiographic evidence of growth disturbances.